Confirmatory Factor Analysis and the Development of a Supply Chain Management for Creating Sustainable Competitive Advantage of Coffee Production in Jember Indonesia - Bagus Putu Yudhia Kurniawan; Sri Sundari; Irma Wardati (International Journal of Supply Chain Management, 2019)
Abstract- Purpose of this research is to investigatethe factors contributing to the Sustainable Competitive Advantage (SCA) for the largest coffee producers in Jember, East Java, Indonesia based on the supply chain management.The Methode of the research has the element of survey research type one, with the combination of exploratory and confirmatory or explanatory research. This study uses a census method or complete enumeration, which is carried out on all members or elements of the population totaling 84 people. The analysis technique used in this study is the Confirmatory Factor Analysis (CFA) and pathanalysis. The result shows that the most powerful indicator as innovation measurement is leadership orientation, while the weakest one is the source of external innovation. The strongest indicator of marketing performance variable is the level of customer growth, while the weakest one is the level of sales growth. The strongest indicator as a variable measuring SCA is durability, while the weakest one is the facility of matching strategic assets owned by the company. Innovation has a direct, positive, and significant effect on marketing performance. Innovation has no significant effect on SCA, however, through marketing performance, the indirect effect of innovation on SCA is significant. Marketing performance has a direct, positive, and significant effect on SCA.